SUSTAINABLE LIFESTYLE DAN PEMANFAATAN LIMBAH ANORGANIK DI SMP MUHAMMADIYAH KOTA DUMAI - Mesra, Trisna; Fitra, Fitra; Saputra, Juni; Abdillah, Nuryasin; Hafrida, Lis; Simanullang, Sanco (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
A lot of waste is generated from students' activities while at school. A simple effort that can be made to minimize waste at school is to recycle inorganic waste. Students need to be given training on waste management. In this community service program, the training participants were 36 class VII students of Muhammadiyah Middle School, Dumai City. The method of service activities uses lecture, discussion and practice methods. The activity steps are a lecture to explain the study of waste, types and sources of waste, waste management using the 3R principle (Reduce, Reuse, Recycle), then continued with questions and answers, demonstrations and practices for recycling inorganic waste (bottles, cans and cardboard) into useful product. This training program can increase female students' awareness, especially regarding waste recycling, so that in the long term it is hoped that it can minimize waste and improve the skills of Muhammadiyah Middle School students in making ecobrick-based creativity